Efektivitas Model RME-Budaya Aceh Berbantuan Artificial Intelligence dalam Konteks Pascabencana di Sekolah Dasar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the effectiveness of the Realistic Mathematics Education model based on Acehnese culture assisted by Artificial Intelligence in improving elementary school students’ numeracy literacy in a post-disaster context. This research is motivated by the low level of students’ numeracy literacy and the suboptimal implementation of contextual learning and technology utilization in mathematics instruction. In post-disaster conditions, learning challenges become more complex, requiring adaptive, contextual, and technology-based learning innovations. This study employed a quantitative approach with a quasi-experimental design using a One Group Pretest-Posttest Design. The subjects of the study were 28 students at UPTD SD Negeri 4 Bireuen. Data were collected through tests, observations, and documentation. Data analysis was conducted using normality tests, paired sample t-tests, and N-Gain calculations to determine the level of improvement in students’ numeracy literacy. The results showed a significant improvement between pretest and posttest scores with a significance value (p < 0.05). The average numeracy literacy ability of students increased from low to moderate and high categories. The N-Gain results were in the moderate to high category, indicating that the implemented learning model was effective. In addition, observational results showed improvements in students’ learning activities, motivation, and engagement. Based on these findings, it can be concluded that the RME model based on Acehnese culture assisted by Artificial Intelligence is effective in improving elementary school students’ numeracy literacy in a post-disaster context. This model integrates contextual approaches, local wisdom, and technology synergistically, thereby creating meaningful, adaptive, and innovative learning. This study is expected to contribute to the development of mathematics education and serve as a reference for educators in implementing context-based and technology-enhanced learning.